A prospective study of cytomegalovirus and herpes simplex virus disease in renal transplant recipients. Issue 11 (November 1982) - Walker, D P; Longson, M; Mallick, N P; Johnson, R W
Abstract : A prospective study of 84 renal graft recipients demonstrated cytomegalovirus (CMV) disease after transplantation in 37% of patients. Reactivation infection was found in 20 of 44 patients (46%) who were seropositive for CMV prior to transplant and primary CMV disease occurred in 11 of 40 (28%) initially seronegative patients. Nearly all cases of primary disease (91%) were associated with symptoms and in these cases CMV was probably acquired via the donated kidneys. Only 35% of the reactivation infections were associated with clinical symptoms. Actuarial life tables indicated that CMV disease did not reduce the length of graft survival. Herpes simplex virus (HSV) infections were diagnosed in 44 (52%) of the patients and included a fatal case of disseminated disease associated with hepatitis.